Alla ricerca dell'„Arcadia degli artisti": il viaggio in Italia di Józef Ignacy Kraszewski - De Carlo, Andrea F. (Wydawnictwo Naukowe UAM, 2007)
In 1858 J. I. Kraszewski accomplished a trip around Italy, a country defined by Goethe as the artists' Arcadia. His trip was described in his travel diary Kartki z podróży 1858-1864 (Travel pages 1858-1864). Kraszewski's aims as an artist and art critic were to deepen his theoretical knowledge, to see the Antique Rome, since he was fascinated by archeology and history, and visit Dante's city, because he had translated The Divine Comedy around 1864.
In search of "artists' Arcadia": Józef Ignacy Kraszewski's trip around Italy
Keywords: Kraszewski J.I.; Italy; Kartki z podróży 1858-1864; Artists' Arcadia